Formal semantics for interactive music scores: a framework to design, specify properties and execute interactive scenarios - Toro, Mauricio; Desainte-Catherine, Myriam; Rueda, Camilo (Journal of mathematics and music (Society for Mathematics and Computation in Music), 2014)
Most interactive scenarios are based on informal specifications, so that it is not possible to formally verify properties of such systems. We advocate the need for a general and formal model aiming at ensuring safe executions of interactive multimedia scenarios. Interactive scores (is) is a formalism based on temporal constraints to describe interactive scenarios. We propose new semantics for is based on timed event structures (TES). With such a semantics, we can specify more properties of the system, in particular, properties about execution traces, which are difficult to specify as constraints. We also present an operational semantics of is based on the non-deterministic timed concurrent constraint calculus and we relate such a semantics to the TES semantics. With the operational semantics, we can describe the behaviour of scores whose timed object durations can be arbitrary integer intervals.